Durkheim's Social Solidarity and the Division of labour: An Overview - Siti Ikramatoun; Khairun Nisa; Khairulyadi Khairulyadi (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2022)
This article aims to review Durkheim's concepts of division of labour and social solidarity, especially how social solidarity developed through the division of labour and how the interplay between the two gives rise to the functionality of the social system. This study, too, explains the relevance of such concepts to studying contemporary society. This study concludes that some underlying shortcomings need addressing without denying Durkheim's attempt to provide a sound methodological and theoretical foundation for sociology as a discipline. Durkheim's contention that the Division of labour forms social solidarity is deterministic and subscribes to the law of rigidity. Individuals' occupational function is seen as a determinant and therefore has nothing to do with human free will and individuals' subjectivity to meaning. It is a sort of reductionism because it eliminates the entire propensity of human nature. It reduces the conditions of society to that of the organism of a living being. As a result, it is tough to replicate Durkheim's solidarity model to explain the complex nature of current urban societies.